IMPLEMENTASI MODEL PROTOTYPE DALAM RANCANG BANGUN SISTEM INFORMASI MANAJEMEN PROYEK (SAMAR) BERBASIS WEB BAGI PERUSAHAAN KONTRAKTOR - Wanty Eka Jayanti; Eva Meilinda; Kiky Fitriana (Jurnal Informatika Kaputama (JIK), 2021)
The project management information system is a system that functions as a company internal planning and control which includes the use of resources, technology, documents and producing information as needed. randang build system in this study implements a prototype software development model. prototype is a basic working model as software development. However, there are some things that may not be known about the prototype by the general public. Meanwhile, the data collection techniques used during this study were carried out by conducting online observations, interviews, and literature reviews. these techniques are carried out online given the pandemic conditions that are still hitting Indonesia. This system is expected to help the company to control and manage the projects that are obtained. The data that will be processed in this system design includes supplier data, financial revenue data, financial expenditure, and project tax reporting data.